Potent Antibacterial and Antibiofilm Activities of a Synthetic Remineralizing Preparation of Nano-Hydroxyapatite Against Cariogenic Streptococcus mutans Using an Ex-vivo Animal Model - El-Gar, Yasmeen H. Abo; Etman, Wedad M.; Genaid, Thuraia M.; Al-Madboly, Lamiaa A. (Frontiers in Dental Medicine, 2022)
Aim The aim to this study is to evaluate the biocompatibility and antibiofilm actions of two nano-hydroxy apatite (NHA). Methodology Nano-hydroxy apatites are biomaterials use in direct contact with living tissues. Therefore, they should be tested for their safety beside assessment of their minimum inhibitory (MIC) and minimum bactericidal concentration (MBC) using broth microdilution method. One hundred and twenty extracted bovine incisors were collected and cleaned to ensure the absence of any defects. Enamel blocks with different size (2 × 2 × 3 mm) and (5 × 5 × 2 mm) were prepared from their labial surfaces using an isomet saw. Enamel blocks are used for detecting the suitable concentration will be used in the following experiments using energy dispersive X-ray analysis (EDX). The remaining enamel blocks divided into 5 equal groups to detect inhibitory effect against bacterial adhesion to the initial enamel caries like lesions using viable count technique beside the antibiofilm activity against mature biofilm of Streptococcus mutans (S. mutans) using confocal laser microscopy. The remaining enamel blocks were used as a representing data for detecting surface topography for each group by using the scanning electron microscopy (SEM). Result The data showed safety of NHA suspensions. Additionally, only NHA suspension of large nanoparticle size (NHA-LPS) had MIC of 1.25 mg/ml against S. mutans. Also, have the higher percentages of Ca and P in the enamel blocks. Furthermore, the lowest level of bacterial adhesion was recorded in (group III) treated by NHA-LPS which was non-significantly different with the positive control group V. Biofilm thickness in group IV treated with NHA-small particle size (SPS) recorded high biofilm thickness followed by group III. Interestingly, group III showed greater killing effect against mature biofilm which is slightly higher than the positive control group V. In group III, surface topography revealed very smooth enamel surface with closed pores. Accordingly, NHA-LPS suspension had antiadhesive, antibacterial, and antibiofilm effect against cariogenic S. mutans representing a promising possibility to be recommended for safe effective remineralization.